The relationship of contraceptive use of KB pills with changes in acceptors' weight at Umbulharjo I health center - Sudrajat Tiyan Mujiono Zuhair; Dwi Rizkita Leonny; Wijayanti Sukirto Novi; Agita Huttomo Muhammad; Hashifah Khairina; Rahmatulloh Irfan (BIO Web of Conferences)
Contraception or anti-conception is an action that can be taken to prevent pregnancy. Birth control pills are an example of a popular hormonal contraceptive in Indonesia. The Contraceptive Prevalence Rate (CPR) or the level of contraceptive device users in Indonesia continues to increase from year to year from 57% in 1997, then based on the Demographic Survey in 2020, it reached 61.78% usage. Apart from the benefits, contraception certainly has several side effects, one of which is changes in body weight. The aimed of this study was to determine the relationship between the use of contraceptive pills with the changes in of acceptors’ body weight at the Umbulharjo I Community Health Center. Research was conducted using quantitative research methods with an analytical survey design using a cross-sectional approach. The sampling technique used in this research was accidental sampling using minimum data, namely 30 samples. Statistical analysis using the paired samples correlation test shows a significance value of 0.00, 0.000<0.005, and the paired sample t-test value obtained a sig (2-tailed) 0.03, 0.003<0.005. From the results above, it can be concluded that there is a significant relationship and there is a difference in average weight before and after using contraceptive pills.